An enhanced SHERPA (E-SHERPA) method for human reliability analysis in railway engineering. (November 2021) - Catelani, Marcantonio; Ciani, Lorenzo; Guidi, Giulia; Patrizi, Gabriele
Abstract: According to the European standard EN 50126 human reliability is a fundamental requirement in railway engineering. Notwithstanding that there are only few methods specifically developed for railway field. Trying to fill this gap, this paper proposes a human reliability analysis technique customized on railway applications to simulate a time-dependent model of the human error probability during the work shift. The first novelty of the proposed method is the use of customized task types for railway applications within a third-generation method. Furthermore, the concept of Eustress is considered to evaluate the impact of the stress on the operator performances by means of the Yerkes-Dodson law. The main novelty of the proposed method is the introduction of a simulator which provides the possibility of considering one or more breaks in the work shift allowing to simulate the error probability based on the duration of the break. The maintenance operations carried out on an Italian Automatic Train Protection System have been taken as case study to validate the proposed method in different scenarios. The results illustrate how a break during the working shift of the operator influences the probability of committing an error. Highlights: Dynamic third-generation HRA method for railway engineering. Time-dependent model which describe the human error probability. Dynamic model of the effects of breaks within the work shift. Yerkes-Dodson law and eustress concept model the effect of stress on the operator. Human error probability estimated for maintenance operations in railway.